Mid‐term outcomes of a male retro‐urethral, transobturator synthetic sling for treatment of post‐prostatectomy incontinence: Impact of radiotherapy and storage dysfunction. Issue 4 (26th July 2016) - Habashy, David; Losco, Giovanni; Tse, Vincent; Collins, Ruth; Chan, Lewis
Abstract : Purpose: To determine mid‐term durability of the AdVance sling for post‐prostatectomy incontinence (PPI) and impact of prior radiotherapy and storage dysfunction. Method: Eighty men undergoing AdVance sling for PPI during 2008–2013 were reviewed. Pre‐op urodynamics, pre and post‐op pad usage, prior radiotherapy, and PGI‐I scores were recorded. Result: Mean follow‐up was 36 months (range 14–72). Twelve men had radiotherapy pre‐op, 10 had detrusor overactivity (DO), and 20 reduced compliance. Pre‐op mean 24‐hr pad weight was 264 g and mean pads‐per‐day (PPD) 2.60 ± 0.29. In the early post‐op period (3–6 months), mean PPD was 0.40 (SD 0.16); at mid‐term follow‐up mean PPD was 1.02 ± 0.31. Radiotherapy and DO were independently predictive of poor mid‐term outcome. Men with DO or radiotherapy were using 1.03 ± 0.42 ( P  = 0.019) and 1.17 ± 0.41 ( P  = 0.02) more PPD, respectively than men without these factors. At mid‐term follow‐up, men without radiotherapy or DO were using 1.98 ± 0.28 less PPD compared to pre‐operatively ( P  < 0.0001); with radiotherapy or DO men were using 0.73 ± 0.38 ( P  = 0.057) and 0.72 ± 0.43 ( P  = 0.092) less PPD, respectively. PGI‐I score for men without radiotherapy or DO was 1.98 ± 0.40 ("much better"); with radiotherapy or DO PGI‐I score was 3.80 ± 0.49 ("no difference"). Conclusion: The AdVance sling provides mid‐term improvement in men with PPI. However, men with radiotherapy or DO have significantly poorer outcomes with mid‐term results indicating a return to baseline degree of incontinence. Caution should be taken when considering the AdVance sling in these men. Pre‐op urodynamics in men with radiotherapy and/or overactive bladder may be important when considering men for AdVance sling. Neurourol. Urodynam. 36:1147–1150, 2017 . © 2016 Wiley Periodicals, Inc.